Amblystegium serpens (Hedw.) Schimp. (Amblystegiaceae: Bryophyta) from Indian Peninsula - Manju, Chandrasekharan Nair; Aswathy, Thekkanangil; Pournami, Kondaram Valappil; Rajesh, Kavile Parambil (Asian Journal of Biological and Life Sciences, 2017)
Amblystegium serpns of the family Amblystegiaceae is reported for the first time from Western Ghats of Kozhikode district and this report forms the first collection from Peninsular India.
Keywords: Amblystegium serpens; Indian Peninsula; New record; Western Ghats